2022
DOI: 10.20527/flux.v19i3.13593
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Caffeine Content in Roasting Temperature Variation of Robusta Luwak Coffee from Garahan Jember Plantation using UV-Vis Spectrophotometry Method

Abstract: ABSTRAK-Kualitas kopi yang dijual ke pasaran dengan jumlah permintaan yang terus meningkat perlu diuji untuk menjamin bahwa pengguna mendapatkan kopi dengan kualitas yang tinggi. Penelitian ini dilakukan dengan tujuan untuk mengetahui kandungan kafeina dari masing-masing sampel kopi dengan variasi suhu sangrai. Kopi yang digunakan adalah kopi luwak Robusta murni dan kopi luwak Robusta campuran beras. Penelitian ini dilakukan dengan menggunakan variasi suhu sangrai yaitu dengan suhu sangrai sebesar 190⁰C dan 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Cahyono et al used a UV-Vis spectrophotometer to measure the absorbance at a wavelength of 200-400 nm. [8].…”
Section: Chlorogenic Acid and Caffeine Extraction Measurement And Cal...mentioning
confidence: 99%
See 1 more Smart Citation
“…Cahyono et al used a UV-Vis spectrophotometer to measure the absorbance at a wavelength of 200-400 nm. [8].…”
Section: Chlorogenic Acid and Caffeine Extraction Measurement And Cal...mentioning
confidence: 99%
“…Caffeine is an alkaloid compound in the form of a white powder, odorless, bitter taste, and somewhat tricky in water but readily soluble in chloroform [12]. Previous studies showed that the maximum absorbance of caffeine standard solution was at a wavelength of 273 nm [8]. Caffeine standard solution measured at wavelengths of 200-400 nm is shown in Figure 4.…”
Section: Absorbance and Linearity Of Standard Caffeinementioning
confidence: 99%